Modification of the Development of Children's Fitness Cards and Fitness Love Board for Down Syndrome School-Age Children in the Fit 5 Special Olympics Progam - Yohanes Giovani Pion Makung; Gigih Siantoro; Abdul Rachman Syam Tuasikal (BIRCU, 2021)
From the lock down condition, Down Syndrome children who are used to activities at school become lazy to do fitness exercises at home, while parents also increase their activities by accompanying their children while at home from morning to night. For this reason, it is necessary to provide a home fitness training program for Down Syndrome children by doing the Fit 5 Special Olympics program. And it is necessary to make a Fitness card and a fitness love board so that children with Down syndrome are more excited. The purpose of this study is to establish cooperation between physical education teachers and parents in maintaining the fitness of Down Syndrome children while at home, and to help maintain the fitness of Down Syndrome children during the lock down period this year and in the coming years if there is a lock down period. again. The subjects of this study were 3 Down syndrome students from Special Olympics Surabaya. The design of this research is development research with research instruments in the form of validation sheets and video recordings that will be used to draw descriptive conclusions. The data analysis technique used is descriptive. Product trial validation was carried out by 6 experts who have experience in treating children with Down syndrome and 3 parents of students. The results showed that the average validation score of the experts was 98% and the average validation score of the parents was 98% which was in the very good category. And it was concluded that the fit card and the love child fit board are fit for mass production. Suggestion for all of us is never to force a Down syndrome child to be willing to follow fitness movements according to our wishes, but let them do it themselves according to their own abilities.